The cytotoxicity assessment of different clear aligner materials - I-Lin Lo; Chuan-Yi Kao; Tsui-Hsein Huang; Chun-Te Ho; Chia-Tze Kao (Elsevier, 2024)
Background/purpose: Invisible orthodontic treatments are becoming increasingly popular, and numerous brands of invisible aligners are now available. However, concerns remain about the safety of the materials used in these products. This study aimed to assess the cytotoxic effects of both original and thermoformed thermoplastic materials used in orthodontic aligners on human periodontal ligament (HPDL) cells in vitro. Materials and methods: The experiment used six different brands, each containing three types of thermoplastic materials, Polyethylene terephthalateco-1, 4-cyclohexylenedimethylene terephthalate (PETG), thermoplastic polyurethane (TPU), and copolyester polyethylene terephthalate (PET). The original sheets and the thermoformed materials were soaked in a culture medium for seven and fourteen days, and then applied to cultured human periodontal ligament cells. Cells were harvested on the first, third, and fifth days after application, and their viability was analyzed using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] assay. Results: The findings revealed that some thermoformed materials, notably PETG, exhibited lower survival rates compared to their non-thermoformed versions. However, other materials such as TP and PET maintained over 70% cell viability, indicating only minor cytotoxic effects. Conclusion: These findings highlight the need for further research into the long-term biocompatibility of these materials but generally affirm their safety for use in orthodontic aligners under the tested conditions.